Debt Brake: Putting the Potential Output Estimation Method to the Test - ZG Überblick (Wirtschaftsdienst)
Abstract The coalition agreement of the federal government states that there needs to be a review of the details of the debt brake, especially the rules for determining the production potential. In particular, the methodology for calculating cyclical deficits is being discussed, as this is decisive for the possible level of new debt. The characteristics that such a methodology should have is disputed. A fundamental point of criticism of the current procedure is its revision sensitivity and procyclicality, which tends to lead to an underestimation of cyclical deficits.